PERANCANGAN SISTEM INFORMASI MANAJEMEN GUDANG DI PLN ULP AMPERA - Muhammad Iqbal; Muhamad Kadafi (Jurnal Riset Sistem Informasi, 2026)
Warehouse management is an important aspect in supporting operational activities at PLN ULP Ampera, particularly in maintaining the availability of electrical materials and equipment. However, the warehouse management process, which is still carried out manually, causes several problems such as errors in recording incoming and outgoing goods, difficulties in monitoring stock in real time, and delays in generating reports. This study aims to design a web-based Warehouse Management Information System that can improve the efficiency, accuracy, and effectiveness of inventory management at PLN ULP Ampera. The research method used is Object-Oriented Analysis and Design (OOAD) with a Unified Modeling Language (UML) approach to model system requirements and design. The research stages include requirement analysis, system design, design validation, and preparation of the system blueprint. The results of this study are in the form of a web-based warehouse management information system design equipped with features for managing item data, recording incoming and outgoing goods transactions, monitoring stock in real time, managing users, and generating automatic reports in the form of tables and graphs. The system is also designed using a three-tier architecture consisting of front-end, back-end, and centralized database layers. Based on the results of the study, the designed system can improve data recording accuracy, accelerate administrative processes, and support the digitalization of material management within PLN ULP Ampera.